Implikasi Border Crossing Agreement dan Border Trade Agreement Terhadap Konektivitas di Wilayah Perbatasan Indonesia-Filipina - Burhan Niode; Ismail Rachman; Welly Waworundeng (Intermestic: Journal of International Studies, 2022)
This study aims to describe the implications of BCA and BTA on the development of population and trade connectivity in the Indonesia-Philippines border area within the framework of the BIMP-EAGA cooperation. Descriptive-qualitative method was used in this study. This study shows that border crossers often carry out illegal border crossings to the Southern Philippines because they carry merchandise and are far from the Border Crossing Entry and Exit Station, and cross-border agreements between Indonesia and the Philippines cannot limit population and trade connectivity in the Indonesia-Philippines border area because the cross-border route used by border crossers is a traditional route. To develop connectivity in the border areas of Indonesia-Philippines, BCA and BTA need to be revised. Sangihe and Talaud Islands Regencies need to function as buffer and transit areas within the framework of the BIMP-EAGA cooperation because the two regencies are geographically close to the Southern Philippines.